DORA BRUDER AS AN AUTOBIOGRAPHICAL WRITING OF PATRICK MODIANO - Mira Utami (Frasa)
Trauma become a part of memory in human life in regard with past. The form of trauma as an emotional scar inside an individual can follow the heirs, reflected in the life of later generations. It also happens in literature, as a way to unconsciously share the traumatic events, as the result of author memories. Dora Bruder is a novel by Patrick Modiano which is written as the way to release the experience of diffculties in the past that likely become his trauma. This research will describe the condition of Dora Bruder as an autobiographical novel of Modiano because it is happened to share the same difficulties, such as a bad-term relationship with family and lost family members. The research is based on theory of Memory by Anne Whitehead and Postmemory by Marianne Hirsch.